Bioinspired Green Synthesis of Nanomaterials and their Applications - Gao, Shuyan; Li, Zhengdao; Zhang, Hongjie (Current Nanoscience, 2010)
The field of nanotechnology spans the synthesis of nanoscale matters, understanding/utilizing their exotic physicochemical and optoelectronic properties, and organization of nanoscale structures into predefined superstructures. Over the past decade, researchers in various fields of chemistry have been studying novel methods through which the morphology and the dimensions of inorganic materials can be controlled at the micro- or even the nano-scopic level. As far as the synthesis of nanoparticles is concerned, there is an evergrowing need to develop clean, non-toxic, and environmentally friendly (“green chemistry”) synthetic procedures in the pursuit of nanotechnology, especially for nanoproducts targeted at bioapplications. Thus, during the last few years, “green” has become a common term to designate those nanomaterials with the aim of replacing nondegradable and toxic regents, thereby reducing the environmental pollution. Biological processes have recently been considered as possible methods for the synthesis of nanoparticles, especially the development of “reen” synthetic approaches. The advantageous features of the biomolecules' applications in nanomaterials green synthesis are that they possess the ability to guide the oriented growth of organic or inorganic substances, and are thermally and chemically stable, easy to obtain, cheap, and, most importantly, environmentally friendly. Combined with traditional chemical techniques, the biomolecules- assisted synthesis method has proven promising in the generation of a large variety of inorganic structures that are currently unattainable through any other methods. Herein, we review the biomolecules-assisted green synthesis of nanomaterials in this context, which covers our recent interesting results and mainly includes (1) nanomaterials obtained by biomolecules-assisted green method, (2) growth mechanism, and (3) their properties.
Keywords: natural nanocomposites